Three-dimensional multiscale simulation on fracture behaviors of cylindrical shells subjected to inner pressure and surface laser irradiation. (April 2017) - Zhang, Rui; Ma, Songsong; Tang, Zhiping
Multiscale numerical simulation has important advantages in analyzing the partial fracture problems of shell structures subjected to the coupled thermo-mechanical effects. The multiscale time–space model of a cylindrical shell subjected to inner pressure and surface laser irradiation by coupling the three-dimensional discrete element method (DEM) and the shell finite element method was established. By simulating the crack-bifurcation extending behaviors of the aluminum alloy cylindrical shell and comparing the fracture behaviors and the calculation time by the multiscale time–space model with those by the multiscale space model of the overlapping element/node, the multiscale time–space model not only satisfies the requirement of simulation accuracy, but also enhances the calculation efficiency greatly under the condition of stable simulation. The multiscale time–space model was applied to the simulations in the fracture behaviors of the aluminum alloy and the 30CrMnSiA steel cylindrical shells under four modes of action. The failure modes of cylindrical shells under different modes of action are directly related to the radius of the laser spot, the power density of the laser, and the extensibility of material. At the same time, the damage evolution process of the cylindrical shells under four modes of action was analyzed through the crack ratio in the mesoscopic DEM elements. The multiscale time–space model provides a reliable analytical way to the complex partial fracture mechanical problems of large-scale cylindrical shell structures subjected to inner pressure and surface laser irradiation. PACS. 02.70.Dh, 02.70.Ns, 42.62.Cf, 46.50.+a, 61.82.Bg, 62.20.mm, 07.05.Tp, 83.60.Uv